ANALISIS PENGELOLAAN PIUTANG PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI BADAN PENDAPATAN DAERAH KABUPATEN SUBANG PADA TAHUN 2018-2020 - ANDRIAN RAMADAN; DIAN ANITA (GANEC SWARA, 2022)
Indonesia is a country where most of its income comes from the tax sector. Based on Law No. 28 of 2009 local taxes are fully delegated to local governments to be managed, one of which is the land and building tax. The problems that occurred in the Subang Regency Regional Revenue Management Agency where there was an increase in the amount of land and building tax receivables during 2018 - 2020. The method used was descriptive qualitative, in which the researcher tried to provide an accurate description and explanation of the problems encountered. The data taken are based on primary and secondary data, the data collection technique in this thesis uses interview, observation, and documentation techniques. As for the data analysis technique, the writer performs data reduction, data presentation, final conclusion and verification. The results of this study indicate that the management of land and building tax receivables at the Regional Revenue Agency of Subang Regency, includes activities for eliminating rural land and building tax receivables (PBB-P2), conducting searches on taxpayers, cooperating with the Subang district public prosecutor's office in order to summon taxpayers who do not pay PBB taxes, cooperate with BPKP. There are still many taxpayers who have not paid their taxes, this factor is due to the lack of awareness of taxpayers, after that the Bapenda carried out several strategies so that people pay their taxes